AN EXPERIMENTAL STUDY ON THIN-LAYER DRYING DRYING CHARACTERISTICS OF APPLE SLICES - Soydan, M.; Doymaz, I (PLAPIQUI(UNS-CONICET), 2021)
In this experimental study, cultivar of Granny Smith apple slices were dried by using convective hot air tray dryer. Before drying process, the pretreatment methods with ascorbic acid and citric acid solution (0.5% + 0.5%), blanching (80 degrees C and 1 min) and potassium carbonate solution (4%) were carried out. Control samples were dried naturally without any pretreatments. Temperatures for hot air convective drying were decided as 50, 60, 70 and 80 degrees C with constant air velocity of 2 m/s in the cabinet dryer. Throughout the drying process, constant drying period was not observed. Once the temperatures increased from 50 to 80 degrees C, drying rate also increased. Well- known mathematical models such as Henderson & Pabis, Page, Midilli & Kucuk, Wang & Singh and Agbashlo et al. were compared with each other to specify the change of moisture inside the material. Consequently, Midilli & Kucuk model was chosen the best model to explain the drying characteristics of the samples with all drying conditions. Diffusivity coefficients of the moisture transfer inside the apple slices at different temperatures were calculated with the help of Fick's second law of diffusion. The values of diffusion coefficients over the mentioned temperature range changed between 4.804.10-10 m(2)/s and 1.739.10-9 m(2)/s. The activation energy values of the drying process were calculated by Arrhenius type equation and found to be 36.1, 32.5, 29.8 and 32.1 kJ/mol for potassium carbonate, citric acid and ascorbic acid mixture, blanching and control samples, respectively.
Keywords: Convective drying; apple drying; mathematical modeling; pretreatment; activation energy; Engineering